Shrinking small towns in Serbia - Ljubenović, Milica (Revija za geografijo, 2025)
Serbian territorial policies actively supported small towns during the socialist period, fostering growth. However, the post-socialist transition brought socio-political changes, economic restructuring, and widespread depopulation. Subsequent territorial policies have largely neglected the development of small towns, resulting in urban shrinkage across much of the country. This paper examines the developmental challenges facing small towns in Serbia, focusing on their current position within national spatial policy and planning framework. Drawing on European spatial policy and theoretical insights, the research aims to: 1) identify the primary obstacles to development of small shrinking towns; and 2) explore potentials for policy improvement. The findings highlight the need for a more targeted and strategically aligned policy framework to revitalize Serbia's small towns.
Keywords: krčenje mest; Mala mesta; prostorska politika; shrinking town; spatial policy; urban policy; urbanistična politika